Phase-rectified signal averaging method to predict perinatal outcome in infants with very preterm fetal growth restriction- a secondary analysis of TRUFFLE-trial - Lobmaier, SM; van Charante, N; Ferrazzi, E; Giussani, DA; Shaw, CJ; Müller, A; Ortiz, JU; Ostermayer, E; Haller, B; Prefumo, F; Frusca, T; Hecher, K; et al. (Elsevier, 2016)
Background Phase-rectified signal averaging, an innovative signal processing technique, can be used to investigate quasi-periodic oscillations in noisy, nonstationary signals that are obtained from fetal heart rate. Phase-rectified signal averaging is currently the best method to predict survival after myocardial infarction in adult cardiology. Application of this method to fetal medicine has established significantly better identification than with short-term variation by computerized cardiotocography of growth-restricted fetuses. Objective The aim of this study was to determine the longitudinal progression of phase-rectified signal averaging indices in severely growthrestricted human fetuses and the prognostic accuracy of the technique in relation to perinatal and neurologic outcome. Study Design Raw data from cardiotocography monitoring of 279 human fetuses were obtained from 8 centers that took part in the multicenter European “TRUFFLE” trial on optimal timing of delivery in fetal growth restriction. Average acceleration and deceleration capacities were calculated by phase-rectified signal averaging to establish progression from 5 days to 1 day before delivery and were compared with short-term variation progression. The receiver operating characteristic curves of average acceleration and deceleration capacities and short-term variation were calculated and compared between techniques for short- and intermediate-term outcome. Results Average acceleration and deceleration capacities and short-term variation showed a progressive decrease in their diagnostic indices of fetal health from the first examination 5 days before delivery to 1 day before delivery. However, this decrease was significant 3 days before delivery for average acceleration and deceleration capacities, but 2 days before delivery for short-term variation. Compared with analysis of changes in short-term variation, analysis of (delta) average acceleration and deceleration capacities better predicted values of Apgar scores <7 and antenatal death (area under the curve for prediction of antenatal death: delta average acceleration capacity, 0.62 [confidence interval, 0.19e1.0]; delta short-term variation, 0.54 [confidence interval, 0.13e0.97]; P¼.006; area under the curve for prediction Apgar <7: average deceleration capacity <24 hours before delivery, 0.64 [confidence interval, 0.52e0.76]; short-term variation <24 hours before delivery, 0.53 [confidence interval, 0.40e0.65]; P¼.015). Neither phase-rectified signal averaging indices nor short-term variation showed predictive power for developmental disability at 2 years of age (Bayley developmental quotient, <95 or <85). Conclusion The phase-rectified signal averaging method seems to be at least as good as short-term variation to monitor progressive deterioration of severely growth-restricted fetuses. Our findings suggest that for short-term outcomes such as Apgar score, phase-rectified signal averaging indices could be an even better test than short-term variation. Overall, our findings confirm the possible value of prospective trials based on phase-rectified signal averaging indices of autonomic nervous system of severely growth-restricted fetuses.